2007
DOI: 10.1101/gad.437107
|View full text |Cite
|
Sign up to set email alerts
|

The PAS/LOV protein VIVID controls temperature compensation of circadian clock phase and development in Neurospora crassa

Abstract: Circadian clocks are cellular timekeepers that regulate aspects of temporal organization on daily and seasonal time scales. To allow accurate time measurement, the period lengths of clocks are conserved in a range of temperatures-a phenomenon known as temperature compensation. Temperature compensation of circadian clock period aids in maintaining a stable "target time" or phase of clock-controlled events. Here we show that the Neurospora protein VIVID (VVD) buffers the circadian system against temperature fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 60 publications
2
55
0
Order By: Relevance
“…The vvd mutation delays the phase of the first band in DD and this effect is more prominent at lower temperatures; VVD may normally act to compensate for temperature effects on the rate of conidiation (Hunt et al 2007). Vvd mutants show an exaggerated phaseresetting response to light pulses, consistent with the function of wild-type VVD in downregulating rapid responses to light (Heintzen et al 2001).…”
Section: Ircadian Rhythms Are Biological Rhythms Withmentioning
confidence: 64%
See 1 more Smart Citation
“…The vvd mutation delays the phase of the first band in DD and this effect is more prominent at lower temperatures; VVD may normally act to compensate for temperature effects on the rate of conidiation (Hunt et al 2007). Vvd mutants show an exaggerated phaseresetting response to light pulses, consistent with the function of wild-type VVD in downregulating rapid responses to light (Heintzen et al 2001).…”
Section: Ircadian Rhythms Are Biological Rhythms Withmentioning
confidence: 64%
“…This establishes a function for VVD as an activator of some light-induced genes, and it may be the absence of this function that allows the vvd mutant strains in our experiments to express a rhythm of conidiation in LL. Hunt et al (2007) have proposed a role for VVD in the conidiation output pathway, and this may explain the activation of continuous conidiation, rather than rhythmic conidiation, in LL in vvd 1 . The loss of VVD protein in the vvd mutants would remove this activation function of VVD and allow expression of the conidiation rhythm in LL.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence suggests that VVD regulates the transcriptional activity of the WCC in mediating photoadaptation in constant light as well as several other properties associated with the circadian clock under free-running conditions (7,21,24,26). Despite the genetic relationship between VVD and the WCC, biochemical studies examining their physical interaction and subcellular localization have not shown direct interactions or colocalization.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function vvd mutants were originally identified by the unique appearance of the bright orange conidia while grown in constant light (23), presumably attributable to the persistent activation of carotenoid biosynthesis (7). In addition to its function in attenuating the direct light response in Neurospora, VVD has been shown to take part in regulating various circadian clock properties, most likely through its effects on the WCC, including gating of light input to the clock (21), maintenance of the clock during the light phase (24,25), and temperature compensation of the circadian phase (26). Despite accumulating genetic and molecular evidence supporting the connection between VVD and WCC, no mechanistic explanation for the relationship has been proposed.…”
mentioning
confidence: 99%
“…Although several interesting models have been developed, and clock genes have been shown "to be important" for temperaturecompensation, the mechanisms are not understood on a molecular level (Huang et al 1995;Leloup and Goldbeter 1997;Sawyer et al 1997;Ruoff et al 2005;Hunt et The natural light/dark and temperature cycles are considered to be the most prominent factors that synchronize circadian clocks with the environment. Understanding the principles of temperature entrainment significantly lags behind our current knowledge of light entrainment in any organism subject to circadian research.…”
Section: Introductionmentioning
confidence: 99%